STATE OF DIAGNOSIS AND TREATMENT OF PATIENTS WITH OVARIAN CANCER IN KRASNODAR KRAI IN 2005-2014 - M. G. LEONOV; S. A. BELYAEVA; S. N. CHERNOV (Кубанский научный медицинский вестник, 2017)
Aim. To study the features of the diagnosis of ovarian cancer in the territory of a large agro-industrial region of Russia – Krasnodar Krai. Materials and methods. Materials for the study were data from the Population Cancer Registry of Krasnodar Krai, as well as the statistical registration form No. 1090/y "Notification of a patient with a first-time diagnosis of cancer or other malignant neoplasm". Based on data on 5 583 newly diagnosed patients with ovarian cancer for the period 2005-2014, in Krasnodar Krai, the analysis of the dynamics of the main indicators of diagnostic quality (morphological verification, stepwise diagnosis, advanced stage of disease, one-year mortality, preventive detection, etc.) taking into consideration the particular qualities of territorial location in the large agro-industrial region of Russia. The analysis of methods of treatment for the patients with ovarian cancer which are subject to special treatment was carried out for the ten-year period. Results. Analysis of the dynamics of the main indicators of the diagnosis of ovarian cancer in Krasnodar Krai for 2005- 2014 showed that the specific gravity of the morphological verification of the diagnosis in 2014 was 88.7% that is 3.1% lower than the average Russian indicator (91.5%). The level of diagnosis of ovarian cancer in the I-II stage increased by 1.5 times and amounted to 33.3% in 2014, with an average Russian indicator of 37.1%. The level of late diagnosis (III-IV stage) was higher than the Russian average by 8.9%. A low level of active diagnosis of ovarian cancer was registered, which was 15.7%, which is 13.2% lower than the Russian average (18.1%). Conclusion. Recommendations are given to practical public health services to improve the quality of medical care for patients with ovarian cancer in Krasnodar Krai.